Application of Canva Media to Improve Science Learning Outcomes for Class V MI Darussalam Students - Rahayu, Puput Sri; Rejeki, Rejeki; Yanti, Apria Linda; Agustina, Lidia (STKIP Rokania Pasir Pangaraian, 2023)
This research aims to determine the application of Canva media to improve science learning outcomes for class V MI Darussalam students. In the learning process in class v MI Darussalam the teacher does not use learning media so that learning is not fun. Learning from teachers is only abstract because teachers rarely use media when teaching students, so learning is boring. The research subjects were 18 class V students. The research results were from 18 students. test results for class V MI Darussalam students in science learning. From the results of cycle 1, it is determined how many students completed and did not complete. However, there are more students who did not complete compared to those who completed. There were 8 students who completed it while there were 10 students who did not complete it. From the results of the second cycle test, learning results were achieved with 77% complete compared to the higher results of test 1 which was 55% incomplete. From cycle 1, eight students did not complete, after the second test only 4 students remained who did not complete. From the results of tests that have been carried out, improving student learning outcomes using Canva media has been successful